2004
DOI: 10.1191/0961203303lu530xx
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in Tunisia: demographic and clinical analysis of 100 patients

Abstract: There is a wide variation in the natural history of systemic lupus erythematosus (SLE) among different ethnic and geographical groups. Studies in Arabs are few and those in North Africans and especially in the Tunisian population do not exist. This study aims to demonstrate the demographic, clinical and laboratory characteristics of SLE Tunisian patients and to identify those at high risk for renal and neuropsychiatric involvements. One hundred patients with SLE (American College of Rheumatology criteria), see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
66
5
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 26 publications
27
66
5
2
Order By: Relevance
“…To our knowledge, only four studies dealing with demographic, clinical and laboratory features of SLE Tunisian patients have previously been reported. [3][4][5][6] However, these studies focused on nonrepresentative groups of the Tunisian population. So, no systematic review can be made to determine the incidence and characteristics of SLE in Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only four studies dealing with demographic, clinical and laboratory features of SLE Tunisian patients have previously been reported. [3][4][5][6] However, these studies focused on nonrepresentative groups of the Tunisian population. So, no systematic review can be made to determine the incidence and characteristics of SLE in Tunisia.…”
Section: Introductionmentioning
confidence: 99%
“…En otra serie, realizada en 100 pacientes tunecinos, la enfermedad activa (60%) e infecciones (40%) fueron las causas más comunes de mortalidad. Las infecciones más frecuentes fueron sepsis bacteriana e infecciones urinarias (28) . Dentro de las referencias nacionales, en una tesis realizada en el Hospital Nacional Cayetano Heredia, entre 1970 y 1990, donde se comparó las historias clínicas de pacientes varones y mujeres con LES, se observó que no hubo diferencias significativas en cuanto a la edad de inicio de la enfermedad, número de criterios al momento del diagnóstico, duración del seguimiento, cuadro clínico, exámenes de laboratorio, actividad extrarrenal, tratamiento y mortalidad.…”
Section: Discussionunclassified
“…9,10 In some previous studies, the incidence was found as 89% females and 11% males and 92% women and 8% men. 11,12 Antibodies to many clotting factors have been described in patients with SLE, including factors VIII, IX, XI, XII and XIII. 13 Acquired inhibitors to other coagulation fac-tors, including factors IX, XI, XIII, vWF protein, and the vitamin K-dependent proteins are extremely rare.…”
Section: Discussionmentioning
confidence: 99%